THE BANK RECONCILEMENT. - Byrnes, Thomas W. (The Accounting Review, 1944)
The article presents information on bank reconcilement. The agreement of the cash balances in banks as they appear in the books of record with the amounts shown to be on deposit by the statements of those banks at certain dates involves different procedures under dissimilar circumstances. The bookkeeper-cashier of a business concern follows the procedure of making necessary adjustments for items in transit or in process of collection omitted in error from either the bank's statement or his employer's records. The auditor however, is interested in more than this mere arithmetical agreement of the two balances. An important initial procedure is the comparison of each paid check returned by the bank with the individual debit charged on the bank statement. This step may be omitted, or reserved for the final procedure in the event of a remaining unallocated difference. If the client's bank statements and paid checks, with other debit and credit memoranda, are sent by the bank to the auditor's office. Deposits also require the careful attention of the auditor, not only in checking the daily totals lodged in the banks, but also in the comparison of the details of some of the daily deposits as indicated in the cashbook with the details as shown on the deposit slips in the possession of the banks.